Dynamics of Conflict Management Research in the Public and Private Sectors: A Bibliometric Analysis - Nanny Mayasari; Ade Suhara; Sri Dinarwati; Mochamad Heru Riza Chakim; Agustinus Talindong (Westscience Press, 2024)
This bibliometric analysis explores the evolving landscape of conflict management research across various dimensions, including thematic clusters, research trends, emerging opportunities, and author collaborations. Utilizing VOSviewer for visual mapping, the study identifies key themes such as leadership styles, resolution processes, and personal traits like gender and professional roles that dominate the discourse. A longitudinal analysis from 2002 to 2010 highlights a pivotal shift from foundational conflict management concepts towards addressing broader societal impacts and understanding the economic ramifications of conflict. Opportunities for future research were pinpointed in underexplored areas such as ethnic conflicts, the costs associated with conflict, and the roles of power in achieving peace. The author collaboration network, though sparse, reveals central figures that could drive further interdisciplinary studies. This study not only maps the current state of conflict management research but also sets the stage for future explorations that could bridge theoretical gaps and enhance practical applications.